Two cases of dermatomyositis: so equal and so different - Cardoso, Ana Rita (2009)
Dermatomyositis is a rare systemic autoimmune disease, which usually presents with muscular weakness and typical rash. With adequate treatment 90% of the patients are alive 5 years after the diagnosis. However, in one group of these patients, dermatomyositis is part of a paraneoplasic syndrome and, in this one, the treatment response decreases and the prognosis is worse. The authors present clinical cases of two 68 year old men, with muscular weakness, dysphagia and typical rash, but with different treatment response and clinical results which mirrored the influence of an associated neoplastic disease on the course of dermatomyositis.